“Socioanalisi”: primi elementi per una riformulazione della teoria sociale come analisi critica della sociazione - Giorgio Grossi (Quaderni di Sociologia, 2018)
Starting from deep-rooted crisis of contemporary social sciences, we need to reformulate our theoretical approach in order to enhancing interpretative knowledge of our social realities. The first step of this analytic program is to deconstruct the historical paradigm of “critical theory” as a hypostatic way to explain social reality in its totality. From this perspective I propose a passage from “critical theory” to “socioanalysis” seen as an analytical-descriptive process without standardization. From this point of view the analysis of sociation (socioanalysis on the analogy of psychoanalysis) is always a critical approach to social reality because its explicative frame is not “prescriptive” but only “possible” (that is polyvalent). In this analytical context we have to confront with concept of ambivalence. This means that “things are in one way but they also are in another way”: existence, social life, interaction, agency, thought cannot be unequivocally interpreted. From this point of view I discuss two examples of contemporary theories that are implicitly ambivalent: the non-critical theory of Bruno Latour and the pragmatic theory of criticism of Luc Boltanski.